KIF1C Variants Are Associated with Hypomyelination, Ataxia, Tremor, and Dystonia in Fraternal Twins. (17th July 2019) - Marchionni, Enrica; Méneret, Aurélie; Keren, Boris; Melki, Judith; Denier, Christian; Durr, Alexandra; Apartis, Emmanuelle; Boespflug-Tanguy, Odile; Mochel, Fanny
Background: KIF1C (Kinesin Family Member 1C) variants have been associated with hereditary spastic paraplegia and spastic ataxia. Case report: We report fraternal twins presenting with cerebellar ataxia and dystonic tremor. Their brain MRI showed a hypomyelinating leukoencephalopathy. Whole exome sequencing identified a homozygous KIF1C variant in both patients. Discussion: KIF1C variants can manifest as a complex movement disorder with cerebellar ataxia and dystonic tremor. KIF1C variants may also cause a hypomyelinating leukoencephalopathy.